All Precursors Are Not Equal: Morphology Control via Distinct Precursor-Facet Interactions in Eu3+-Doped NaLa(WO4)2 - Rastogi C.K.; Saha S.; Kusuma V.; Pala R.G.S.; Kumar J.; Sivakumar S. (My University, 2025)
Morphology of lanthanide (Ln3+)-doped nanostructures plays a crucial role in determining the crystal-field-dependent luminescent properties as that modulates the surface-to-bulk ratio of Ln3+ ions. In this work, we demonstrate a systematic morphology control in Eu3+-doped sodium lanthanum tungstate NaLa0.95Eu0.05(WO4)2 by varying lanthanide precursor salts and report variation in its photoluminescence properties. Chloride and nitrate salts of lanthanide produce nanoneedles and -cuboids, respectively, whereas acetate and carbonate salts produce rugby ball-like morphology. Density functional theory-based simulations have been performed to study the effect of growth hindering species (Na salts of precursor anions, i.e., Cl-, NO3 -, CO3 -2) in controlling the evolution of low index (100) and (001) facets of NaLa0.95Eu0.05(WO4)2. The changes in morphology are correlated with the preferential development of low index (100) and (001) facets caused by differential adsorption of growth hindering species. Accordingly, they attach with La-sites of (100) rather than an O-terminated (001) facet; binding selectivity order being chloride > nitrate > carbonate. Strong adsorption of chloride salts on (l00) causes anisotropic growth along [001] direction and leads to needle morphology due to vast stacking of basal planes. The minor binding difference in adsorption of nitrate salts observed on (100) and (001) facets is responsible for overall growth and evolution of cuboid morphology. The binding of carbonate (or acetate) salts on (100) is weak, and combined evolution of (001), (011), and (100) facets leads to rugby ball morphology. Further, the needle, cuboidal, and rugby shape particles produce different UV sensitized emission with the Commission Internationale de I' Eclairage (CIE) chromaticity coordinates as (0.44, 0.25), (0.48, 0.26), and (0.59, 0.32), respectively. © 2019 American Chemical Society.